1987
DOI: 10.1002/art.1780301205
|View full text |Cite
|
Sign up to set email alerts
|

Folate status of rheumatoid arthritis patients receiving long‐term, low‐dose methotrexate therapy

Abstract: The folate status of 29 healthy control subjects, 16 rheumatoid arthritis (RA) patients taking methotrexate (MTX), and 20 RA patients who were not being treated with MTX was estimated by an assay of the folate‐dependent enzymatic synthesis of serine from formate and glycine, which is termed the C1 index. Analysis of variance demonstrated that the specific activity of the enzyme system in lymphocytes was significantly lower in the MTX‐treated group, with an activity approximately one‐half that of the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 52 publications
2
16
0
1
Order By: Relevance
“…Consistent with studies of MTX therapy in rheumatoid arthritis, we found that JIA patients on MTX therapy have a pronounced reduction in circulating folate concentrations (26, 27, 39-43). Reductions in folates occurred despite supplementation with folic acid in 47% of patients receiving MTX.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with studies of MTX therapy in rheumatoid arthritis, we found that JIA patients on MTX therapy have a pronounced reduction in circulating folate concentrations (26, 27, 39-43). Reductions in folates occurred despite supplementation with folic acid in 47% of patients receiving MTX.…”
Section: Discussionsupporting
confidence: 88%
“…[20][21][22] However, as MTX may exert part of its pharmacological effects through folate depletion, it might be expected that folic acid supplementation would also decrease MTX efficacy. Although some studies have investigated the contribution of folate supplements to the effects of MTX, 18 23 reports are controversial, and the effects of folate PG levels on MTX efficacy are not clearly established.…”
mentioning
confidence: 99%
“…There have been some proposed devices of dosage regimens for leucovorin utilized during MTX therapy [1,2], and, several papers have been published documenting the successful administration of FA to patients taking MTX, as an attempt to lessen the incidence of induced folate deficiency syndromes [7,4]. However, it was documented that the coadministration of pyrimethamine (PYR) and FA amplifies the decrease of plasma 5-MF levels in rats [4], resulting in the aggravation of fetal toxicity due to PYR [16].…”
Section: Plasma and Urine Kinetics Of 5-mfmentioning
confidence: 99%
“…Folinic acid (leucovorin) is fully reduced, one carbon substituted, stable folate derivative that can act to reverse the adverse effects of MTX administration. Stenger et al [13] state, however, that as folinic acid bypasses dihydrofolate reductase, the specific dosage regimen is much more critical, to maintain efficacy and to reduce the adverse side effects, than for the fully oxidized folates, pteroylglutamic acid or folic acid (FA).There have been some proposed devices of dosage regimens for leucovorin utilized during MTX therapy [1,2], and, several papers have been published documenting the successful administration of FA to patients taking MTX, as an attempt to lessen the incidence of induced folate deficiency syndromes [7,4]. However, it was documented that the coadministration of pyrimethamine (PYR) and FA amplifies the decrease of plasma 5-MF levels in rats [4], resulting in the aggravation of fetal toxicity due to PYR [16].…”
mentioning
confidence: 99%